Translation and technocracy in development: Defining the potentials and limitations of translation technology for Maya inclusion in Guatemalan development - Riemland, Matt (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2022)
This article attempts to determine the role that translation technology might play in effective, indigenous-led development practices. It uses the Maya in Guatemala as an example. Guatemala has seen the growth of a robust non-governmental organization (NGO) sector that implements technocratic, neoliberal development strategies and has historically excluded Maya input (Raxche’, 1996). Mayan languages are a key focus in Maya efforts to assert their autonomy in Guatemala (French, 2010, p. 5). Language barriers still render vital resources inaccessible to the Maya (Fischer-Mackey et al., 2020, p. 906), and few Guatemalan NGOs emphasize Mayan languages in their work (Henderson et al., 2014, p. 80). Translation, therefore, is an essential component of effective and inclusive development practices. Whereas best practices in commercial translation are becoming increasingly intertwined with technology (Rico Pérez, 2019, p. 116), translation technology remains largely absent from humanitarian work (p. 119). Despite the opportunity this gap presents, the implementation of information and communication technology (ICT) such as neural machine translation (NMT) may exacerbate existing power imbalances between technocratic development planners and their intended beneficiaries (Chipidza & Leidner, 2019, p. 153). This article uses a meta-analytical approach in assessing existing research on the subject to illustrate the ways in which language and translation are integral to three key development areas: intercommunity meetings, the health sector, and environmental and social impact assessments (ESIAs). It uses Chipidza and Leidner’s (2019, p. 160) theory of power parity in the implementation of ICT to propose ways in which NMT may serve alternative, more inclusive development strategies in these specific contexts. The article details possible solutions to the anticipated practical challenges of implementing NMT in these contexts; and it highlights the limitations of each NMT application. It serves as a roadmap for implementing translation technology in inclusive development strategies for indigenous communities.